INSTAGRAMABLE TOWN - Yanuar, Andri; Aufa, Naimatul (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Instagramable Town is designed to meet the needs of tourist attractions in Banjarbaru that can accommodate a variety of photo spot facilities which are again favored by millennials. The solution to the problem taken on Instagramable design takes a photogenic concept in architecture by applying natural settings, signage, lighting, murals, tiles & textures. the photogenic concept in architecture is expected to provide a place that can accommodate a variety of photo spot facilities which are again favored by the millennial generation.